Screenomics: A Framework to Capture and Analyze Personal Life Experiences and the Ways that Technology Shapes Them. (4th March 2021) - Reeves, Byron; Ram, Nilam; Robinson, Thomas N.; Cummings, James J.; Giles, C. Lee; Pan, Jennifer; Chiatti, Agnese; Cho, Mj; Roehrick, Katie; Yang, Xiao; Gagneja, Anupriya; Brinberg, Miriam; et al.
Abstract : Digital experiences capture an increasingly large part of life, making them a preferred, if not required, method to describe and theorize about human behavior. Digital media also shape behavior by enabling people to switch between different content easily, and create unique threads of experiences that pass quickly through numerous information categories. Current methods of recording digital experiences provide only partial reconstructions of digital lives that weave – often within seconds – among multiple applications, locations, functions, and media. We describe an end-to-end system for capturing and analyzing the "screenome" of life in media, i.e., the record of individual experiences represented as a sequence of screens that people view and interact with over time. The system includes software that collects screenshots, extracts text and images, and allows searching of a screenshot database. We discuss how the system can be used to elaborate current theories about psychological processing of technology, and suggest new theoretical questions that are enabled by multiple timescale analyses. Capabilities of the system are highlighted with eight research examples that analyze screens from adults who have generated data within the system. We end with a discussion of future uses, limitations, theory, and privacy.